Synthesis, evaluation of drug delivery potential, and the quantum chemical investigation on a molecular imprinted polymer for quetiapine antipsychotic; a joint experimental and density functional theory study - Hoseini chehreghani, Seyyedeh Fatemeh; Aberoomand Azar, Parviz; Shekarchi, Maryam; Daraei, Bahram (Frontiers in Chemistry, 2022)
In this project, the quetiapine drug was used as the template for synthesis of the molecular imprinted polymer. The polymerization approach for preparation of this composite was the precipitation method. Where, the methacrylic acid (MAA) was used as the functional monomer, ethylene glycol dimethacrylate (EGDMA) was applied as the cross linker, and 2,2-azobisissobutyronitrile (AIBN) as the initiator. The scanning electron microscopy (SEM) showed that the diameter of the nanoparticles is about 70 nm. The adsorption rates of quetiapine to MIP host were evaluated at different pHs, and results showed that the highest adsorption values were obtained at pH=7. Moreover, the kinetics of adsorption process detected to follow the Langmuir isotherm (R2 = 0.9926), and the Pseudo-second-order kinetics (R2 = 0.9937). The results showed a high capability of synthesized molecular imprinted polymers as pharmaceutical carriers for quetiapine. Finally, in the light of DFT-based quantum chemical descriptors, the polymer- quetiapine drug system was designed and investigated. The results showed that there is a strong interaction between the host (polymer), and the guest (drug), due to several hydrogen bonds, and polar interactions.